Stretchable Devices: Donut‐Shaped Stretchable Kirigami: Enabling Electronics to Integrate with the Deformable Muscle (Adv. Healthcare Mater. 23/2019). Issue 23 (5th December 2019) - Morikawa, Yusuke; Yamagiwa, Shota; Sawahata, Hirohito; Numano, Rika; Koida, Kowa; Kawano, Takeshi
Abstract : Stretchable electronics are significantly used to integrate electronic devices with soft biological tissues. However, conventional stretchable devices have limited applications because of their higher Young's modulus and instability in wet environments. In article number 1900939, Takeshi Kawano and co‐workers propose a donut‐shaped‐kirigami device that can envelop the muscle, allowing the device to stretch and follow muscle deformation and robust EMG signal recordings.